Pengaruh Pelatihan Kebersyukuran Terhadap Resiliensi Pada Penderita Kanker Payudara - Saputro, Iswan; Sulityarini, Rr. Indahria (Unisia, 2018)
This study aimed to determine whether gratefulness training increased the breast cancer patient’s resilience. The design of this experiment research was one-group pretest-posttest design with a follow up. The subject consisted of 2 breast cancer patients in Yogyakarta. The data were analyzed quantitatively using descriptive analysis. To strengthen the quantitative data, the researchers also used observation and interview to obtained qualitative data. The gratefulness training module was based on the gratitude theory from Al-Jauziyah (2010). Resilience measured using the Connor-Davidson Resilience Scale (CD-RISC) with 27 items that have been modified by Dong, et al. (2013) (Cronbach’s Alpha = 0,88). The results showed that gratefulness training increased the breast cancer patient’s resilience.